Transformational leadership: journal club for emergency and intensive care nurse managers - Maria Valéria Pereira; Wilza Carla Spiri; Regina Stella Spagnuolo; Carmen Maria Casquel Monti Juliani
ABSTRACT Objectives: to understand the meaning of transformational leadership and develop an educational intervention addressing this theme. Methods: content analysis and action research for the collective construction of an educational intervention addressing management practices and their association with transformational leadership. The setting was the emergency and intensive care network, and nine nurse managers participated in the research. Data was collected from recorded and individualized interviews, and by using the journal club strategy. Results: the unveiled themes were: factors related to the team, to the leadership processes and to the leader. Difficulties in decision-making and planning processes were revealed; the leader needs to work in teams, which in turn should be appropriately sized. The journal club and planning model used provided the praxis of this work. Final Considerations: reflection and training for the development of transformational leadership were fundamental to solidify the decision-making processes involved in the managers' practice.